(untitled) (Palíndromo, 2024)
The objects and solutions that result from design projects are often conceived to go unnoticed by their users, silently intertwined with everyday life practices. However, in a design exhibition, the products of design activity are necessarily highlighted. In such occasions, in order to be able to appreciate the exhibition proposal, what approach could we take to analyze or to “read” the languages of the pieces being shown? This work is based on the foundations of Discursive Semiotics, including its developments into Sociosemiotics, Plastic Semiotics and the studies of aesthesis. Our goal is to review the main semiotic contributions that have been given to the study of museums and art exhibitions, aiming to assess whether (and how) these theoretical-methodological tools could serve as a foundation for the analysis of design exhibitions. As a result, we propose an analytical pathway structured in four successive and hierarchical reading dimensions – object, exhibition, cultural institution, territory –, highlighting at each stage what is specific to design projects, that therefore should be taken into account when dealing with the analysis of a design exhibition.